The death of utopian politics in mid-nineteenth-century France or what the Icarians can tell us about QAnon, conspiracy, and our political moment. Issue 4 (8th August 2022) - Sipe, Daniel
ABSTRACT: In this era of Pizzagate, QAnon, and "Stop the Steal, " where has utopian thinking gone? The historical analysis that I propose to undertake here will suggest that our current state of affairs (and its concomitant anxieties) are, at least in part, an outgrowth of the historical developments that saw utopia and its anticipatory fictions mostly driven from the political arena. In their place, there has emerged a dark ecosystem of dystopias wrought of conspiracy – stories posing as anti-fictions that function by instrumentalizing the ambiguities of the past to weave a nightmarish version of our "real reality." To begin to understand how dystopia and its narrative forms have come to permeate the political arena, we might return to mid-nineteenth-century France, where a comparable climate existed that can serve as a sounding board for our troubling times. In this essay, I show how there emerged a movement that so thoroughly enmeshed its political aspirations with fictional praxis that the two became wholly indistinguishable. They were the Icarians and their fantasy, long before QAnon and 8kun, is that of our political modernity. In examining the cultural war that erupted with Icarians' intriguing embrace Etienne Cabet's 1840 utopian novel, Voyage en Icarie, we might hope to gain critical perspective on our own political moment.